Fiscal Incentives in Federations: Russia and the US Compared. Issue 4 (December 2016) - Alexeev, Michael
I compare fiscal incentives in Russia and the US according to the conventional measures employed in the relevant literature. Although Russia is more fiscally centralized as measured by shares of budget expenditures and revenues, measures of fiscal incentives at the margin are largely similar in the US and Russia both at the regional and municipal levels. These results are contrary to the estimates obtained for Russia in the earlier literature. It appears that fiscal federalism reforms undertaken in Russia throughout the 2000s improved fiscal incentives of subnational governments. However, these results should be treated with great caution as fiscal incentive measures employed in this paper and in the literature at large are far from perfect. This might provide an explanation for the result that intraregional fiscal incentives do not have a significant effect on economic growth.